Hydration Characteristics of Excess-sulfate Titanium Gypsum Slag Cement - Yong JIANG; Cheng LIU; Guomin WANG; Maojie WU; Yun JIANG (Kuangchan zonghe liyong)
This is an article in the field of mineral materials. Based on the experience of cementing materials composited with industrial by-product gypsum and slag , several sets of excess-sulfate titanium gypsum slag cement were designed, and the water requirement of normal consistency, setting time, mechanical properties and water resistance of the cement were studied, and the hydration products were analyzed by XRD and SEM. The results show that titanium gypsum can increase the water requirement of normal consistency and prolong the setting time, which has an adverse effect on the mechanical properties and water resistance. The adverse effect of titanium gypsum can be compensated by increasing the content of clinker appropriately. When the content of clinker is 25%, the compressive strength of composite cementing material can reach 30 MPa at 28 d. In the experimental group with higher titanium gypsum or clinker content, the hydration products were mainly ettringite and calcium silicate/aluminate hydrate, while in the experimental group with higher content of slag and lower content of clinker, the hydration products were mainly amorphous calcium silicate/aluminate hydrate.